2006
DOI: 10.1007/s11239-006-8669-4
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced thrombocytopenia and thrombosis: Evidence from patients receiving an oral glycoprotein IIb/IIIa inhibitor in the Orbofiban in Patients with Unstable coronary Syndromes- (OPUS-TIMI 16) trial

Abstract: Thrombocytopenia, though uncommon, was associated with orbofiban use and an increased risk of bleeding, but also death and MI. This study provides further evidence that drugs that lead to thrombocytopenia are, in a significant proportion of patients associated with thrombotic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…The percentage of current smokers was lower in the TP group compared to ACS patients without acquired TP in 7 out of 8 studies. 8,9,11,20,2325 Finally, patients with TP had a higher frequency of previous myocardial infarction (7 out of 8 studies 8,9,11,19,2123 ), CABG surgery (6 out of 7 studies 9,11,19,2123 ) and renal insufficiency (3 out of 3 studies 9,20,23 ) (Table 1). No significant differences were observed between groups with regard to treatment with unfractionated heparin, even though this ranged significantly between studies (39.9% to 100% in the TP group versus 40.3% to 100% in the no TP group).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The percentage of current smokers was lower in the TP group compared to ACS patients without acquired TP in 7 out of 8 studies. 8,9,11,20,2325 Finally, patients with TP had a higher frequency of previous myocardial infarction (7 out of 8 studies 8,9,11,19,2123 ), CABG surgery (6 out of 7 studies 9,11,19,2123 ) and renal insufficiency (3 out of 3 studies 9,20,23 ) (Table 1). No significant differences were observed between groups with regard to treatment with unfractionated heparin, even though this ranged significantly between studies (39.9% to 100% in the TP group versus 40.3% to 100% in the no TP group).…”
Section: Resultsmentioning
confidence: 97%
“…8,9,11,1925 Eligible studies were all retrospective analyses derived from ACS clinical trials, except for the study by Gore et al that was based on a global registry for acute coronary events. 22 A total of 134,028 patients without TP vs. 8,133 with TP were included and the overall risk of bias for the primary endpoint of all-cause mortality was found to be moderate in all studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Large clinical studies revealed that thrombocytopenia associated with antiplatelet treatment not only increased risk of bleeding, but also thrombotic events [8]. For the first time, we demonstrated directly relationship between thrombocytopenia and thrombosis (indicated by D-dimer level).…”
Section: Discussionmentioning
confidence: 54%